Relationship between basketball skills and selected components of physical fitness - Brillantes, Rolando C. 1944- (1980)
The purpose of this study was to determine whether there is any relationship between basketball skills and selected physical fitness components. The subjects were 92 basketball players from eight high schools in the provinces of Pampanga, Nueva Ecija and Bulacan. The AAHPHER basketball Skill Test which consisted of eight test events and the ICSPFT Physical Performance Battery were employed in this study. The research concluded that there is no relationship between basketball skills and physical fitness as measured by the AAHPHER Basketball Skill Test and ICSPFT Physical Performance battery. Only four positive and three negative low relationships were established out of the fifty-six pairs of variables.